2017
DOI: 10.1589/jpts.29.245
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of ultrasonography for evaluating trunk muscle size: a pilot study

Abstract: [Purpose] Ultrasonography (US) is widely applied to measure the muscle size in the limbs, as it has relatively high portability and is associated with low costs compared with large clinical devices such as magnetic resonance imaging (MRI). However, the applicability of US for evaluating trunk muscle size is poorly understood. This study aimed to examine whether US-measured muscle thickness (MT) in the trunk abdominal and back muscles correlated with MT and muscle cross-sectional area (MCSA) measured by MRI. [S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 23 publications
5
27
1
Order By: Relevance
“…Kubo et al determined using ultrasonography that AT CSA did not differ between sprinters and untrained subjects. It is well known that magnetic resonance image (MRI) is more appropriate to evaluate tissue size than ultrasonography . Additionally, Bohm et al have reported that there was a lack of a significant correlation between ultrasonography and MRI‐measured AT CSAs.…”
Section: Introductionmentioning
confidence: 99%
“…Kubo et al determined using ultrasonography that AT CSA did not differ between sprinters and untrained subjects. It is well known that magnetic resonance image (MRI) is more appropriate to evaluate tissue size than ultrasonography . Additionally, Bohm et al have reported that there was a lack of a significant correlation between ultrasonography and MRI‐measured AT CSAs.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, we did not perform CT or MRI to evaluate sarcopenia. Nevertheless, very high correlations between ultrasound and MRI-measured thicknesses of RA have been reported: r = 0.932 to 0.963 in non-athletes (P < 0.001); 28 and r = 0.847 to 0.926 in athletes (P < 0.001). 29 Moreover, in several reports on liver cirrhosis, sarcopenia evaluated using CT or MRI has been fairly well predicted by the same surrogate markers that we used: MAMC (AUROC 0.84, P = 0.001; 13 and r = 0.385, P < 0.001 8 ), HGS (r = 0.382, P < 0.001 8 ) and SGA class (in men only marginally P = 0.051; 8 or a modified score in all patients, P < 0.001 13 ).…”
Section: Discussionmentioning
confidence: 99%
“…The US-measured MTs of the trunk muscles were measured by using a B-mode ultrasonographic apparatus (SSD-3500SV; Aloka, Japan) with a linear transducer (scanning frequency; 7.5 MHz). The methods for measuring MTs of the abdominal and back muscles using US have been previously described 16 ) . In brief, the MTs for the RA were obtained from three parts, including the upper RA (URA), central RA (CRA), and lower RA (LRA).…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies are now using US to measure trunk muscle size 12 , 13 , 14 , 15 ) . Therefore, we applied this US technique and then found that the US-measured MT of trunk muscles correlated strongly with MRI-measured MCSA in healthy untrained subjects 16 ) . However, compared with untrained subjects, athletes associated with various sports, especially those involving trunk rotation, have larger trunk muscles 3 , 7 , 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%